2022
DOI: 10.1038/s41598-022-09832-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for undergoing surgery in patients with newly diagnosed open-angle glaucoma

Abstract: Despite the clinical importance of glaucoma surgery, studies on its prevalence and risk factors are limited. We analyzed a database comprising approximately 1,000,000 Korean residents to investigate the prevalence and risk factors for undergoing glaucoma surgery within 5 years of diagnosis with open-angle glaucoma. Of the 4,303 patients evaluated, 226 (5.3%) underwent glaucoma surgery. Factors associated with the likelihood of glaucoma surgery included the use of two or more eye drops (odds ratio [OR], 30.30; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…A similar trend in procedure types was reported in the United States associated with the advent of MIGS since 2012 (Boland et al., 2021). A Korean healthcare insurance claims database study reported a 5‐year surgery rate of 5.3% in newly diagnosed OAG patients (Lee et al., 2022). Similarly, a US claims database study investigating treatment patterns in the first 4 years of OAG reported a cumulative incidence of 5.1% (Schwartz et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar trend in procedure types was reported in the United States associated with the advent of MIGS since 2012 (Boland et al., 2021). A Korean healthcare insurance claims database study reported a 5‐year surgery rate of 5.3% in newly diagnosed OAG patients (Lee et al., 2022). Similarly, a US claims database study investigating treatment patterns in the first 4 years of OAG reported a cumulative incidence of 5.1% (Schwartz et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, the Korean cohort gathered data from 2004 to 2010 of 4560 OAG patients, while the US data from 2007 to 2014 encompassed 6172 OAG patients. Secondly, for case identification we used a medication reimbursement database distinct from studies utilizing hospital billing claims data (Kansal et al., 2020; Lee et al., 2022; Schwartz et al., 2021). Our definition for OAG entails a thorough clinical and administrative process of medication reimbursement claims adhering to standardized criteria effectively precluding glaucoma suspects with inconclusive findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On average, it is estimated that there are 139.2 ± 113.1 glaucoma surgeries performed per million population, and 5.3% of glaucoma patients are likely to receive surgical treatments within five years of their diagnosis. 21 Presently, trabeculectomy is the gold standard for glaucoma surgery, 22,23 which forms a scleral fistula to drain the AH towards the subconjunctival space (outside sclera and beneath conjunctiva), resulting in a filtering bleb. 18,24 Despite its operational simplicity, it is associated with a high rate of complications, 25 a high rate of surgical failure, 26 a high reoperation frequency ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…21 Presently, trabeculectomy is the gold standard for glaucoma surgery, 22,23 which forms a scleral fistula to drain the AH towards the subconjunctival space (outside sclera and beneath conjunctiva), resulting in a filtering bleb. 18,24 Despite its operational simplicity, it is associated with a high rate of complications, 25 a high rate of surgical failure, 26 a high reoperation frequency ( e.g. , 29% within five years), 27 and intensive postoperative management.…”
Section: Introductionmentioning
confidence: 99%